A New Look at Cardiac Defense: Attention or Emotion? - Vila, Jaime Luis; Fernández, María Carmen; Pegalajar, Joaquín; Vera, María Nieves; Sánchez, María B.; Ramírez, Isabel; Ruiz-padial, Elisabeth; Pérez, Nieves; Robles, Humbelina (The Spanish Journal of Psychology, 2003)
The study of cardiac defense has a long tradition in psychological research both within the cognitive approach—linked to Pavlov, Sokolov, and Graham’s work on sensory reflexes—and within the motivational one—linked to the work of Cannon and subsequent researchers on the concepts of activation and stress. These two approaches have been difficult to reconcile in the past. We summarize a series of studies on cardiac defense from a different perspective, which allows integration of the traditional approaches. This new perspective emphasizes a sequential process interpretation of the cardiac defense response. Results of descriptive and parametric studies, as well as those of studies examining the physiological and psychological mechanisms underlying the response, show a complex response pattern with both accelerative and decelerative components, with both sympathetic and parasympathetic influences, and with both attentional and emotional significance. The implications of this new look at cardiac defense are discussed in relation to defensive reactions in natural settings, the brain mechanisms controlling such reactions, and their effects on health and illness